2018
DOI: 10.4025/actasciagron.v40i1.34966
|View full text |Cite
|
Sign up to set email alerts
|

<b>Linkage disequilibrium and population structure in <i>Fragaria chiloensis</i> revealed by SSR markers transferred from commercial strawberry

Abstract: ABSTRACT. The Chilean strawberry [Fragaria chiloensis (L.) Mill.] is the maternal progenitor of the commercial strawberry (Fragaria × ananassa Duch.), which is characterized by fruits with high organoleptic quality and is well-suited to areas where drought and salinity represent a constraint on crop growth and productivity. We examined the patterns of linkage disequilibrium, genetic diversity and population structure among 54 accessions of F. chiloensis to understand the genetic basis of this species. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
(31 reference statements)
0
7
0
1
Order By: Relevance
“…Previous studies have shown low and moderate levels of genetic diversity among F. chiloensis germplasm collections, which generally depend on the size of the collection and the type of molecular marker used [10,16,17]. a general linear model for each trait were used as the adjusted phenotypes for the Bayesian regression, taking into account the effect of genetic structure [10]. All the statistical analyses were performed using the R package MCMCglmm (version 3.6.1; https://www.r-project.org) [15].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown low and moderate levels of genetic diversity among F. chiloensis germplasm collections, which generally depend on the size of the collection and the type of molecular marker used [10,16,17]. a general linear model for each trait were used as the adjusted phenotypes for the Bayesian regression, taking into account the effect of genetic structure [10]. All the statistical analyses were performed using the R package MCMCglmm (version 3.6.1; https://www.r-project.org) [15].…”
Section: Resultsmentioning
confidence: 99%
“…chiloensis f. chiloensis and f. patagonica were defined as previously reported [7,9]. The analyzed accessions (Table S1) correspond to a subset from the germplasm collection evaluated by Mora et al [2] and Oñate et al [10]. Table S1.…”
Section: Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations